Online tax processes implementation and capability of selected taxpayers in Manduriao, Iloilo City - Marivic Villanueva; Rowena Cristina (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
Majority of the population has limited knowledge on taxation and filing of taxes over the counter much more on online filing. The study aimed to determine the level of online tax processes implementation of BIR Iloilo City and the degree of online tax processes capability of selected taxpayers in Manduriao, Iloilo City from November to December 2020. The descriptive-correlational research design and Technology Acceptance Model (TAM was used as support of the study. The model shows haw users come to accept and use the technology. Descriptive and inferential statistics were also used. A researcher-made questionnaire was distributed to randomly select 155 taxpayers in Manduriao, Iloilo City. Data were analyzed and interpreted using the Statistical Package for Social Science Software (SPSS) applying frequency count, percentage, mean. T-test, f-test, analysis of variance and Pearson r were availed to test variances and similarities. Findings highlighted that the BIR level of online tax processes implementation was high as to perceived credibility and ease of use.  The degree of online tax processes capability was high particularly in technical knowledge. There was a significant difference in the level of online tax processes implementation considering highest educational attainment while variation was not evident as to sex, age, business industry and years in business. The level of online tax processes implementation of BIR Iloilo City correlated with the degree of online tax processes capability of selected taxpayers in Manduriao, Iloilo City.